Hydrogen and syngas production from biomass gasification for fuel cell application. Issue 5 (4th March 2018) - Jin, Cheng-Lin; Yang, Ren-Fu; Farahani, Mohammad Reza
ABSTRACT: Gasification process is being developed to produce a clean and efficient gas flue from fuels such as coal, biomass, and solid/liquid wastes for power generation. In this work, a biomass gasification kinetic model that can predict reaction temperature, gasification performance, and gas composition has been developed for a circulating fluidized bed (CFB). Experimental data from a CFB power plant have been used to validate the model. It is confirmed that the addition of steam is important for increasing the hydrogen concentration and syngas caloric value. Based on the predicted results, an optimal condition is suggested for air and steam gasification in the CFB gasifier.